2020
DOI: 10.1021/acs.energyfuels.0c01748
|View full text |Cite
|
Sign up to set email alerts
|

Formation Stages and Evolution Patterns of Structural Fractures in Marine Shale: Case Study of the Lower Silurian Longmaxi Formation in the Changning Area of the Southern Sichuan Basin, China

Abstract: Taking the Lower Silurian Longmaxi Formation in the Changning area of the southern Sichuan Basin as an example, the characteristics and formation stages of tectonic fractures are comprehensively studied by regional scale geological analysis and microscopic scale experimental tests. Regional scale geological analysis shows that there are mainly high-angle and vertical structural fractures, which have the characteristics of small opening, large spacing, small fracture density, and high filling degree. The fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 65 publications
2
38
0
Order By: Relevance
“…The difference of gas-bearing property between the DY2 well and DY1 well in the Dingshan area is mainly caused by the difference in fault development scale and sealing property (Fan et al, 2018). In the analysis of the paleotectonic stress field and preservation conditions in the Changning area, it is confirmed that the faults formed by the Yanshan movement and Himalayan movement are the main fracture forming period (Wang et al, 2017;Fan et al, 2020b). Fault sealing is the direct reason affecting the preservation conditions (Awdal et al, 2013;Gale et al, 2014;Xie et al, 2019;Hou et al, 2020;Li et al, 2021a;Li, 2021;Qie et al, 2021;Wang and Wang, 2021); the distribution of faults and fractures is predicted by means of geophysical and stress field simulation.…”
Section: Introductionmentioning
confidence: 85%
“…The difference of gas-bearing property between the DY2 well and DY1 well in the Dingshan area is mainly caused by the difference in fault development scale and sealing property (Fan et al, 2018). In the analysis of the paleotectonic stress field and preservation conditions in the Changning area, it is confirmed that the faults formed by the Yanshan movement and Himalayan movement are the main fracture forming period (Wang et al, 2017;Fan et al, 2020b). Fault sealing is the direct reason affecting the preservation conditions (Awdal et al, 2013;Gale et al, 2014;Xie et al, 2019;Hou et al, 2020;Li et al, 2021a;Li, 2021;Qie et al, 2021;Wang and Wang, 2021); the distribution of faults and fractures is predicted by means of geophysical and stress field simulation.…”
Section: Introductionmentioning
confidence: 85%
“…The faults in the northeastern part of the study area have long extents and large fault throws, while small faults are mainly developed in the south and west; the main fault strikes are NE and NNW, which are quite different from the fold strike. 10,51,52 The faults in the region are superimposed under the influence of tectonic stresses with multiple stages and directions; this situation has led to multistage and multiform fault and fold combinations, which have great importance for the enrichment of shale gas and improvements in reservoir performance and productivity (Figure 1).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…[6][7][8][9] The sealing property of faults developed in shale reservoirs is one of the key factors determining whether the formed reservoirs can be preserved in an area with complex geological conditions such as the Sichuan Basin, which shows the effects of superimposition of multistage tectonic movements. [10][11][12] In situ stress is a natural stress existing in the crust where no engineering disturbance has occurred and is mainly composed of a self-weight stress field and a tectonic stress field. All geological structures such as joints, faults, and folds indicate crustal rock deformation and fractures caused by tectonic stress.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of countries have been engaged in the exploration of shale gas. Additionally, the subsequent technological innovation has fueled the efficient development of shale gas, and the supporting fundamental geological surveys and development techniques have been advanced (Fan et al, 2020a;Fan et al, 2020b;Hou et al, 2020;Wang H et al, 2020;He et al, 2021). Nevertheless, the commercial development of shale gas has been rarely achieved despite some countries acquiring shale gas via exploration (He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%